Empirical and emerging management of the internal sales space of neighborhood stores in Bogotá - Luis Marquez (GEON Journal (Management, Organizations and Business), 2015)
This article sought to conceptualize from the complex thought with comments and dialogues how the internal space exhibition and sales of agroup of neighborhood shops of the town of Barrios Unidos in Bogota is handled. He left the knowledge and experience of the author andindividual dialogue with a group of shopkeepers in the same town. Through its own language and their interactions, to understand how they handlethe object described, creating a new look at the issue. For this qualitative research methods and data collection, and the observation and depthinterviews where several perceptions emerged, for understanding how the shopkeepers have handled the display and the internal spaces ofstore sales were used
Keywords: Stores neighborhood; empirical and emergent merchandising